(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This research paper examines the field of early childhood education, with a particular focus on the potential of STEAM (science, technology, engineering, arts, and mathematics) technology to develop the intellectual abilities of preschool children. By integrating STEAM principles into the curriculum, teachers can create a dynamic learning environment that encourages critical thinking, problem-solving skills, creativity, and innovation in young learners. This paper highlights the benefits, challenges, and effective strategies for using STEAM technology to develop the intellectual development of preschool children.